Pelatihan Pengolahan Ikan Nila Sebagai Upaya Peningkatan Gizi Dan Pemberdayaan Ibu PKK Di Kelurahan Kandang Panjang - Saefatul Ridwan; Meilita Afiota; Ayu Khusnun Nada; Dewiyanti Mitasari; Melisa; M. Faqiul Kamal; Meila Rizqi Adenia; Ony Garindra Saputra; Muhammad Dicky Syamsuddin; Tri Yusufi Mardiana; Ni’matul Fatihah; Muhammad Aji Al Azhar (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2026)
Tilapia utilization in Kandang Panjang Village is still dominated by simple processing methods, resulting in suboptimal added value and consumption variety. However, tilapia is a source of animal protein that plays a crucial role in meeting family nutritional needs. This community service activity aims to improve the knowledge and skills of PKK (Family Welfare Movement) women in processing tilapia into nutritious, practical, and economically valuable nugget products. The activity implemented a training and hands-on practice approach on December 29, 2025, involving seven participants. The material provided covered the nutritional benefits of tilapia, the importance of food diversification, and the stages of processing tilapia into nuggets. The activity results showed an increase in participants' understanding and skills in the processing process, as well as a positive and enthusiastic response to innovative tilapia processed products. This activity has the potential to encourage increased fish consumption, family food diversification, and the development of household businesses based on local potential.